Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1158/1078-0432.ccr-07-0629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum Mesothelin in Patients with Mesothelioma and Lung Cancer

Abstract: Purpose: High levels of serum-soluble mesothelin family proteins (SMRP) have been found to be associated with malignant mesothelioma (MM), but not lung cancer (LC).To verify the clinical role of this marker for both these tumors, we tested serum SMRP in the largest population of thoracic cancers ever assembled. Experimental Design: SMRP blood concentrations were measured in 107 patients with MM, 215 patients with LC, 130 patients with benign respiratory diseases (BRD), and 262 controls. Statistical comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
107
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 21 publications
(17 reference statements)
13
107
2
Order By: Relevance
“…We also showed that there is a relationship between serum mesothelin level at diagnosis and patients survival [70]. Similar results were also published by Cristaudo et al [72], but other authors did not find such relationship [74].…”
Section: Mesothelinsupporting
confidence: 91%
See 1 more Smart Citation
“…We also showed that there is a relationship between serum mesothelin level at diagnosis and patients survival [70]. Similar results were also published by Cristaudo et al [72], but other authors did not find such relationship [74].…”
Section: Mesothelinsupporting
confidence: 91%
“…Surgery resulted in a sharp decrease in serum mesothelin while chemotherapy induced no change [67]. A significantly larger series from France confirmed the diagnostic utility of mesothelin [69,70] followed by similar results in series from Italy [71,72] and Netherlands [24]. Globally analysed, the results from these different teams showed that serum mesothelin is a good diagnostic marker with areas under ROC curved around 0.8-0.85.…”
Section: Mesothelinmentioning
confidence: 59%
“…Our data, in particular, provide the evidence that high SMRP dosage can be considered as an independent prognostic tool for patients with epithelioid MPM and suggest that this dosage could be useful both as a screening test for diagnosis (11), interpreted, of course, taking into account the other information available to the clinical context.…”
Section: Soluble Mesothelin-related Peptides (Smrp)mentioning
confidence: 54%
“…Other studies (8)(9)(10)(11)(12)(13)(14) confirmed that serum SMRP was a promising marker for diagnosis, prognosis and clinical monitoring of MPM. High SMRP concentrations were detected in all the studies only in the epithelioid and mixed MPM.…”
Section: Soluble Mesothelin-related Peptides (Smrp)mentioning
confidence: 87%
“…No marker discriminates well between Mt and other cancers [19,24], which, in conjunction with uncertainty about progenitor cells [14], makes the demarcation of Mt as an entity indistinct. Mesothelin and osteopontin have been considered promising markers, but both have limitations [18,25,26]. Although several studies indicated that mesothelin is useful for screening, other evidence indicates that this marker has a considerable false-positivity rate [27], being insufficiently sensitive for early diagnostics [28].…”
Section: Page -02mentioning
confidence: 99%